Propriedades magnéticas do sistema de nanopartículas NiFe2O4 + NiO + Fe2O3 sintetizadas pelo método Pechini. - RIBEIRO, Pablo Rafael Trajano. (2013)
The studied material consists of a nanoparticle system of nickel ferrite, nickel oxide and hematite, or NiFe2O4 + NiO + Fe2O3, prepared by the Pechini method through the synthesis of the precursors iron nitrate, ethylene glycol, citric acid and nickel nitrate. We vary the amount of nickel nitrate relative to the initial stoichiometry by preparing samples with 0%, 10% and 20% excess nickel nitrate, in order to vary the amount of NiO in the composition. The formation of NiF e2O4 + NiO + Fe2O3 occurred after heat treatment at 1000K for 1 h. The microstructural analysis was done by XRD x-ray diffraction, M ossbauer spectroscopy and SEM scanning electron microscopy. We also perform analyzes of thermomagnetometry TM and specific heat Cp. The magnetic analysis consisted of hysteresis measurements at temperatures between 300K and 540K using a VSM vibrating sample magnetometer. In addition, ZFC-FC magnetization curves, AC magnetic susceptibility and magnetization over time between 5K and 300K were made using a PPMS in ACMS mode. Among the results, we can highlight the observation of a strong temporal dependence of magnetization (spin-glass relaxation) for temperatures up to 300K, possibly attributed to the super spiral disorder on the surface of NiF e2O4 nanoparticles. This hypothesis is reinforced by ZFC-FC magnetization curves, which show typical spin-coupled crosses at low temperatures.